Finishing aeronautical planetary herringbone gear wheels in container vibrating smoothing machine - Jacek MICHALSKI (Scientific Journal of Silesian University of Technology. Series Transport)
The paper presents the technological process of abrasive-chemical machining wheel bearing surface of the cylindrical herringbone gears planetary gear in vibrating container smoothing machine according to Isotropic Finishing ISF® technology of the REM Chemicals Inc. company. Gear wheels are made of stainless Pyrowear 53 and subjected to carburizing, hardening, cold working and low tempering. The change in value of deviation indicators for the kinematic accuracy, smoothness and geometric structure of the machined surfaces of the gear teeth after smoothing compared with the contoured grinding were analyzed. The findings are different a characteristic performance on the surface of the tooth side along the outline, especially with a higher value at the head of the tooths. This creates a need for appropriate modification of the lateral surface of the teeth in the process of contoured grinding. The results of the mechanical strength of the samples gear wheel after the smoothing process and evaluating the hydrogen embrittlement are presented.